2016
DOI: 10.1021/jacs.6b01377
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Hydrogen Evolution Reaction over Strained MoS2 with Sulfur Vacancies Using Scanning Electrochemical Microscopy

Abstract: Molybdenum disulfide (MoS2), with its active edge sites, is a proposed alternative to platinum for catalyzing the hydrogen evolution reaction (HER). Recently, the inert basal plane of MoS2 was successfully activated and optimized with excellent intrinsic HER activity by creating and further straining sulfur (S) vacancies. Nevertheless, little is known about the HER kinetics of those S vacancies and the additional effects from elastic tensile strain. Herein, scanning electrochemical microscopy was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
211
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(216 citation statements)
references
References 36 publications
2
211
0
3
Order By: Relevance
“…However, several theoretical calculations have suggested that the inert basal planes of MoS 2 can be exploited as potential active sites following activation by heteroatom doping, defect site generation, and strain engineering (Fig. 4) [3949]. For example, heteroatom doping into MoS 2 can produce high dopant concentrations on the surface, thereby modifying the hydrogen absorption strength of nearby surface atoms (Fig.…”
Section: Active Sites In Molybdenum Sulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several theoretical calculations have suggested that the inert basal planes of MoS 2 can be exploited as potential active sites following activation by heteroatom doping, defect site generation, and strain engineering (Fig. 4) [3949]. For example, heteroatom doping into MoS 2 can produce high dopant concentrations on the surface, thereby modifying the hydrogen absorption strength of nearby surface atoms (Fig.…”
Section: Active Sites In Molybdenum Sulfidesmentioning
confidence: 99%
“…Since then, various studies focused on maximizing active edge site densities via structural engineering approaches of MoS x catalysts, including space-confined growth [2225], vertical alignment [2628], nano-assembly [2931], and the design of biomimetic molecular catalysts [3234]. The basal planes of MoS 2 , which were believed to be inert in the HER, have also been successfully activated to show meaningful activity by several strategies, including phase engineering from the 2H phase to the metallic 1T phase [26, 3538], heteroatom doping [3941], defect site generation [4247], and strain engineering [40, 48, 49]. Despite significant investigations into the structural engineering of MoS 2 -based electrocatalysts to enhance the HER performance, a number of questions remain regarding the active sites and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[85,86] Demgegenüber wird die erworbene Spannung durch einen externen Vorgang eingeführt. [82,[92][93][94][95] Die kommerziellen Edelmetall-Elektrokatalysatoren (wie Pt/C) sind üblicherweise teuer,was ihren Vorteilen in der Leistung entgegensteht. Eine Spannungsmodifizierung ist fürd ie erworbene Spannung leichter durchzuführen als fürdie inhärente.…”
Section: Spannungssteuerungunclassified
“…Very recently, several studies reported that the basal plane of MoS 2 was successfully activated by creating sulphur (S)-vacancies. Svacancies introduce gap states that are favorable to hydrogen adsorption [32,33]. Zheng et al [34] reported that the monolayer 2H-MoS 2 by introducing S-vacancies and straining yielded an optimal hydrogen adsorption free energy (∆G H ) equivalent to 0 eV, achieving the highest intrinsic HER activity among molybdenum-sulfide-based catalysts.…”
Section: Introductionmentioning
confidence: 99%